Recent Advances in Ionic Liquids 2018
DOI: 10.5772/intechopen.80062
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Green Solvents for the Stabilisation of Nanomaterials: Imidazolium Based Ionic Liquids

Abstract: For over a decade, ionic liquids (ILs) have attracted enormous attention from scientists across the globe. The history of these compounds traces back to 1914 where the inception of the first IL with a melting point of 12°C was made. Years later, a progression of the remarkable related compounds have been discovered. Out of many analogous compounds realized from time to time, the imidazolium class of ionic liquid is the most studied because of their air and moisture stability. The physicochemical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Both mechanisms create a protective coating around the NPs, thereby hindering their aggregation and control the distribution of their sizes. Judicious selection of the molecular structures of ILBSs is required for fabricating NPs with controlled sizes, shapes and porosity that can be useful in various biological applications and catalysis [ 218 , 219 , 220 ].…”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 99%
“…Both mechanisms create a protective coating around the NPs, thereby hindering their aggregation and control the distribution of their sizes. Judicious selection of the molecular structures of ILBSs is required for fabricating NPs with controlled sizes, shapes and porosity that can be useful in various biological applications and catalysis [ 218 , 219 , 220 ].…”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 99%
“…Protic ILs (PILs) include the inexpensive [HSO 4 ]-based ILs. , Their synthesis entails the transfer of a hydrogen cation from the acid to the base. Aprotic ILs (AILs), which include 1,3-dialkyl imidazolium salts, make up the largest class of ILs . They are often synthesized in two steps, known as the metathesis route: (i) quaternization of amines or phosphines with suitable alkylation agents to form the cation; followed by (ii) metathesis via the addition of a metal or inorganic salt of the desired anion …”
Section: Introductionmentioning
confidence: 99%
“…Aprotic ILs (AILs), which include 1,3-dialkyl imidazolium salts, make up the largest class of ILs. 15 They are often synthesized in two steps, known as the metathesis route: (i) quaternization of amines or phosphines with suitable alkylation agents to form the cation; followed by (ii) metathesis via the addition of a metal or inorganic salt of the desired anion. 16 The metathesis route to AIL is complex and raises concerns over the resulting IL purity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These ILs can also be referred as promising green solvents . Keeping in view the extensive applications of imidazolium-based ILs, , it is vital to shed light on their refolding ability against chemically denatured proteins. Thus, for the present study, two ILs with 1,3-dialkyl imidazolium as cations, namely [Emim]­[ESO 4 ] (IL-1) and [Emim]­[Cl] (IL-2), were taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…These ILs can interact with several biochemical species because of its high directional polarizability as well as hydrophobic or hydrophilic regions . It owns a multitude of useful characteristics such as convenient preparation, high thermal stability, and inertness to water and air. These properties have established the ILs as a novel IL with the potential industrial and pharmacological application. Since then various studies reported the effect of ILs on protein stability.…”
Section: Introductionmentioning
confidence: 99%